Potential of Tannin Extract From Coffee Grounds as an Exfoliant in Ultrasonic-Assisted Graphene Synthesis and Optimized Response Surface Methodology - Bagaskara, Eldo Delta; Nela Mafazah; Muhammad Reza; Sudirman; Fry Voni Steky; Veinardi Suendo (Department of Chemistry, FMIPA, UNEJ, 2026)
Graphene is a carbon-based nanomaterial with excellent electrical, thermal, and mechanical properties, making it very promising for various advanced applications. However, conventional graphene synthesis methods generally involve hazardous chemicals and environmentally unfriendly processes. This study investigated the use of tannin extract derived from coffee grounds as a green exfoliating agent for sustainable graphene synthesis via liquid-phase exfoliation. The effects of graphite:tannin ratio, ultrasonication time, and ultrasonication temperature on graphene formation were evaluated using the Response Surface Method (RSM) with Box–Behnken Design. The synthesized graphene was characterized using UV-Vis spectrophotometry and Raman spectroscopy. The UV-Vis response was represented by Absorption Peak Area (APA), while the quality of the graphene layer was evaluated using the Raman I2D/IG ratio. The results showed that lower graphite:tannin ratios generally resulted in better APA and I2D/IG responses, indicating the important role of tannin in exfoliation and dispersion stabilization through π–π stacking interactions. Longer ultrasonication time improved the exfoliation efficiency by maximizing the cavitation intensity. Qualitative observations after 5 days of storage showed that the dispersion with higher tannin concentration exhibited slower sedimentation and reduced re-stacking tendency. RSM optimization showed optimal parameters at a graphite:tannin ratio of 2 mg/mL, an ultrasonication time of 60 min, and an ultrasonication temperature of 54 °C, resulting in a predicted response of 0.009 for APA and 0.548 for I2D/IG